A Legal Debate on Polygamy: Classical and Contemporary Perspectives - Sukring Syamsuddin (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2018)
The Islamic texts concerning polygamy in the Qur’an, Hadith, and other sources are still in the state of mujmal which have no strict indication to the precise meaning and instruction. The argument can be debated in multi- interpretation frame. In practice, a lot of muslims tend to generalize the application of law of polygamy. It becomes an interesting issue for some Indonesian muslim due to its close relation to the tendency or desire of men to add his wife. Some of them even believe polygamy as one of the Prophetic way (sunnah). This view can historically be refuted, considering that the Prophet did polygamy after Khadījah, his first wife, died. Another fact is that all of the Prophet’s wives are widows whose husbands died in the battlefield, except ‘Aisyah. In addition, the marriage of the Prophet with these women is a part of the God’s special order. In this case, polygamy is an exclusivity for the Prophet and it cannot be viewed as the Prophetic wagons to be applied by his followers. Here there is a difference in the perspective of classical and contemporary Muslim scholars concerning the issue based on their different views on the word of God in QS. al-Nisa’ (4): 3. In principle, the Qur’an allows but does not advocate polygamy. It is in this perspective that some scholars are divided into those who absolutely allow, allow in emergency, those who have moderate understanding, and some who are strict to be conservative, based on their different analytical and methodological issues.[Nash tentang poligami di dalam al-Qur'an, as-Sunnah dan sumber-sumber lain, sifatnya masih umum (mujmal). Dalilnya bisa diperdebatkan dengan multi tafsir, sehingga dalam praktiknya orang menggunakan hukum poligami secara "pukul rata." Terdorong ingin memberikan pemahaman yang lebih rinci. Poligami menjadi perbincangan menarik sebagian masyarakat Indonesia, menarik karena poligami merupakan salah satu kecederungan atau keinginan laki-laki untuk menambah isterinya. Sebahagian pemahaman umat Islam berpendapat bahwa berpoligami merupakan sunnah Rasul. Poligami tidak bisa dikatakan sebagai sunnah Rasul. Sebab Nabi Muhammad saw berpoligami setelah Khadījah isteri Nabi meninggal dunia. itupun dari sekian isteri Nabi saw hanya ‘Aisyah yang masih perawan selebihnya adalah janda-janda yang di tinggal mati suaminya dalam peperangan, dan perkawinan Nabi saw dengan wanita-wanita tersebut atas perintah Allah swt, poligami merupakan kekhususan bagi Nabi saw, jadi tidak boleh berdalih sunnah Rasul. Disinilah kemudian terjadi perbedaan perspektif ulama klasik dan ulama kontemporer tentang poligami yang didasarkan pandangan  mereka terhadap firman Allah swt dalam QS. An-Nisa/4; 3. Pada prinsipnya al-Qur’an membolehkan tapi tidak menganjurkan poligami. Dalam perspektif inilah ada yang membolehkan, ada yang membolehkan secara darurat, ada yang moderat, ada yang ketat (prasyarat), dan yang konservatif masing-masing didasarkan pada kajian analisis dan metodologi yang berbeda-beda.]